The migraine syndrome in children. Issue 10 (October 2022) - Howells, Rachel; Abu-Arafeh, Ishaq
Abstract: Migraine is a brain disorder with complex pathogenesis and aetiology. The clinical presentation of migraine changes with brain maturation during the first 20 years of life. Migraine is typically a paroxysmal disorder with well-defined episodes separated by freedom of symptoms. Despite the variable clinical features of migraine, each episode may have a predictable sequence of phases. The main phase of each episode is characterized by one or more symptoms of severe headache, vomiting, abdominal pain, vertigo and/or torticollis. This phase may be preceded by premonitory and aura symptoms, and followed by a recovery phase and resolution of symptoms. These phases can be clear and well defined in some patients but indistinct and subtle in others. Different migraine presentations share common trigger factors, associated symptoms, relieving factors and family history. This review describes migraine as a primary headache disorder, but with greater emphasis on other forms of migraine in children and young people including abdominal migraine (AM), cyclical vomiting syndrome (CVS), benign paroxysmal vertigo (BPV), benign paroxysmal torticollis (BPT) and infantile colic (IC). We will discuss clinical assessment, diagnostic criteria, investigation (when needed) and treatment for each childhood migraine syndrome.